“Influence of Visual Input and Surface Stability on Gastrocnemius Muscle Activation During Quiet Standing Using Multi-Feature EMG and Bilateral Assessment.” - Saftari, Liana Nafisa; Susanti, Hesty; Randa, Gloria Belinda; Saputra, Latifa Majesta; Azzahra, Ashila Ghaitsa (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
Postural stability depends on multisensory integration, yet most studies focus on a single EMG feature or sensory condition at a time. This creates a significant gap in understanding how multiple EMG features change when various sensory inputs are altered during quiet standing. To address this, the present study examined bilateral medial and lateral gastrocnemius activation using five EMG features: Mean Absolute Value (MAV), Root Mean Square (RMS), Waveform Length (WL), Integrated EMG (IEMG), and Total Power (PT) across four sensory conditions that combine visual input (eyes open or closed) and surface stability (stable or unstable). A one-way ANOVA revealed significant condition effects for RMS, MAV, WL, and IEMG (p < 0.05), while PT showed only a non-significant trend. Paired t-test results indicated that MAV significantly increased on the unstable surface with eyes closed compared to the stable surface (t(4) = 4.793, p = 0.009), WL increased in the right lateral gastrocnemius under the same condition (t(4) = 3.976, p = 0.016), and closing the eyes on a stable surface significantly increased WL in the right medial gastrocnemius (t(4) = 6.209, p = 0.003). Across features, the right gastrocnemius consistently showed greater modulation than the left, suggesting dominance-related asymmetry in neuromuscular control. This study provides one of the first bilateral multi-feature EMG characterizations of sensory perturbations during quiet standing. The findings demonstrate that the absence of vision increases neuromuscular demand even on stable surfaces, and that unstable surfaces further amplify activation, particularly in complexity-related features such as WL. These outcomes highlight the potential of EMG features, especially WL, as objective biomarkers for balance assessment. Clinically, the results may inform rehabilitation and fall-prevention programs by supporting the use of unstable surfaces and vision-restricted exercises to enhance proprioceptive and vestibular compensation